2010
DOI: 10.4103/0019-5413.65149
|View full text |Cite
|
Sign up to set email alerts
|

Role of suture anchors in management of fractures of inferior pole of patella

Abstract: Background:The traditional recommendation for displaced comminuted inferior pole fractures is excision of the comminuted pole followed by reattachment of the patellar tendon with transosseous suture. To the best of our knowledge there has been no previous published study mentioning the use of suture anchors for fracture inferior pole of patella. We present a retrospective analysis of five cases of patients doing well at final follow-up of two years.Materials and Methods:Five patients treated at our institute u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 9 publications
1
25
1
6
Order By: Relevance
“…The functional outcome in different studies shows that fixation with K-wires and basket plate is definitely inferior to excision of patella. 14 These results were consistent with the results reported by study of Anand et al 4 The comminuted fracture of inferior pole of patella was investigated by Chang et al and reported that fixation usually fails and different metal implants does not offer any protection against failure. 13 Excision of the fragments of bone with attachment of the patellar tendon by transosseous pull-out suture is usually indicated when the fragments are severely comminuted.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The functional outcome in different studies shows that fixation with K-wires and basket plate is definitely inferior to excision of patella. 14 These results were consistent with the results reported by study of Anand et al 4 The comminuted fracture of inferior pole of patella was investigated by Chang et al and reported that fixation usually fails and different metal implants does not offer any protection against failure. 13 Excision of the fragments of bone with attachment of the patellar tendon by transosseous pull-out suture is usually indicated when the fragments are severely comminuted.…”
Section: Discussionsupporting
confidence: 88%
“…3 The traditional method of treatment for displaced comminuted inferior pole fractures is excision of the comminuted pole followed by reattachment of the patellar tendon with trans osseous suture. 4,5 The reattachment of the ligament of patella to the proximal cancellous rough surface of fractured patella is controversial. Some trauma surgeons recommend attachment of the ligament of patella near the articular surfaces and others advocate reattachment near the anterior cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Parsiyel patellektomi uygulanacaksa, kuadriseps ve patellar tendon kalın örgü dikişler veya çapa ile patellanın anteriyor korteksine tutturulur. [23] Dikişler düğümlenirken diz 90 derece fleksiyona alı-narak ameliyat sonrası fleksiyon kısıtlılığının önüne geçilmiş olur. Bu gibi durumlarda kemik tendon dizilimini sağlamak önemlidir aksi halde femoral kondiller üzerindeki temas kuvvetleri artar (Şekil 5).…”
Section: Tedavi̇unclassified
“…Because of this, treating this type of fracture poses a special problem [4,5] . Various treatment options include tension band wiring (TBW), circumferential wiring, cancellous screws fixation, fixation of the lower pole augmented by patellotibial SS wire loop, basket loop fixation and excision of the lower pole of the patella [6,7] . The superior fragment is important for effective extensor mechanism and to be preserved.…”
Section: Introductionmentioning
confidence: 99%